Does preoperative steroid treatment affect the histology in giant cell (cranial) arteritis?. Issue 12 (26th July 2012) - Bury, Danielle; Joseph, Jacob; Dawson, Timothy P
Abstract : Introduction: Giant cell arteritis (GCA) has been successfully treated with steroids for many years and temporal artery biopsy (TAB) is regarded as the gold standard diagnostic test. The primary aim of this study was to determine whether steroid pretreatment abrogates histological features of GCA reducing diagnostic return, as suspected on the basis of anecdotal evidence. This impacts upon patients suspected of having GCA and the need for prompt treatment balanced with the diagnostic need for TAB. Methods: A 6-year single-centre retrospective study of biopsies (2005–2011) was performed with interrogation of the medical notes for information regarding steroid use. The null hypothesis considered there was no association between steroid use and biopsy outcome. Results: No significant difference was found between steroid use and biopsy outcome, with biopsies still producing positive results after weeks of steroid treatment. Conclusions: TAB is still useful in the diagnosis of GCA, even after commencing steroid treatment.